2012
DOI: 10.1177/0022219412468160
|View full text |Cite
|
Sign up to set email alerts
|

“Passageless” Administration of the Nelson–Denny Reading Comprehension Test

Abstract: There are few tests that assess reading comprehension in adults, but these tests are needed for a comprehensive assessment of reading disorders (RD). The Nelson-Denny Reading Test (NDRT) has a long-passage reading comprehension component that can be used with adolescents and adults. A problem with the NDRT is that reading comprehension test items can be answered correctly without reading the associated passage. The current study determined how IQ, verbal comprehension, and reading skills were associated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…To accurately measure learners' reading ability, it is first necessary to find an assessment tool that measures the constructs that directly relate to reading comprehension (Ready et al, 2013). According to Treffers-Daller and Huang (2020), the most widely accepted description of the construct of reading comprehension is Gough and Tunmer's (1986) simple view of reading.…”
Section: Assessing Reading Comprehensionmentioning
confidence: 99%
“…To accurately measure learners' reading ability, it is first necessary to find an assessment tool that measures the constructs that directly relate to reading comprehension (Ready et al, 2013). According to Treffers-Daller and Huang (2020), the most widely accepted description of the construct of reading comprehension is Gough and Tunmer's (1986) simple view of reading.…”
Section: Assessing Reading Comprehensionmentioning
confidence: 99%
“…One subtest of the Nelson–Denny requires reading passages and answering multiple choice questions. Ready and colleagues (2013) showed that question accuracy on the Nelson–Denny reading subtest is correlated with fluid intelligence even when participants are administered the test without the associated passages to read (and, thus, may have little to do with actual reading comprehension ability).…”
Section: Resultsmentioning
confidence: 99%
“…Before looking in more detail at the construct of vocabulary and how this can be measured a few words must be said about the measurement of different components of reading. As Ready et al (2012) point out, there are not many reading tests for adults, and even fewer that specifically target adult L2 learners. One of the tests for adult native speakers is the National Adult Reading Test (NART, Nelson, 1982).…”
Section: Reading Comprehension: the Construct And Its Measurementmentioning
confidence: 99%